2022
DOI: 10.1186/s12884-022-04412-9
|View full text |Cite
|
Sign up to set email alerts
|

The optimal period for oocyte retrieval after the administration of recombinant human chorionic gonadotropin in in vitro fertilization

Abstract: Background Our objective was to investigate the existence of an optimal period for oocyte retrieval in regards to the clinical pregnancy occurrence after the administration of recombinant human chorionic gonadotropin (rhCG) (Ovitrelle®). Methods We studied the digital records of 3362 middle eastern couples who underwent in vitro fertilization (IVF) treatment between 2019 and 2021. Results Through stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Furthermore, the results of our meta-analysis also revealed that the clinical pregnancy rates in the long interval group were significantly higher than in the short interval group. More specifically, a recent retrospective cohort study provided some degree of support for our findings, indicating that there is a significant positive correlation between the oocyte retrieval period and the clinical pregnancy occurrence up to the 37th hour, where retrieval at the 37th hour was found to provide the most optimal outcome [ 37 ]. Although there is a difference in clinical pregnancy rates between the two groups, there is no statistically significant difference in miscarriage rates and live birth rates.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, the results of our meta-analysis also revealed that the clinical pregnancy rates in the long interval group were significantly higher than in the short interval group. More specifically, a recent retrospective cohort study provided some degree of support for our findings, indicating that there is a significant positive correlation between the oocyte retrieval period and the clinical pregnancy occurrence up to the 37th hour, where retrieval at the 37th hour was found to provide the most optimal outcome [ 37 ]. Although there is a difference in clinical pregnancy rates between the two groups, there is no statistically significant difference in miscarriage rates and live birth rates.…”
Section: Discussionsupporting
confidence: 57%
“…Controls were postnatal women with neonatal birth weight appropriate for GA delivering consecutive to the assigned cases. Using Naegele's method, GA was determined for cases treated with in vitro fertilization by counting the days since oocyte retrieval or co-incubation and then adding 14 days [ 8 ]. The collection of data was performed by an interview-based technique and by checking the files of the patients for both cases as well as the control group at the time of discharge of the patient and/or baby.…”
Section: Methodsmentioning
confidence: 99%